The Impact of Parental styles of socialization on Social Interactions of Male and Female Children in Primary Grades - Al-Asmari, Manar Ali; El-Maghraby, Randa Mohammed; Bajamal, Huda Fuad (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify Parental styles of socialization and their impact on children’s social interactions between males and females in primary grades. To achieve this goal, the researchers used a qualitative approach to study the phenomena. The study sample consisted of four families, each including one parent and one child in early childhood, bringing the total number of participants to eight: four parents (two fathers and two mothers), and four children (two boys and two girls). A semi-structured interview method was used to collect data. The study results revealed a variety of Parental styles of socialization, ranging from verbal to nonverbal. Verbal styles included the use of blaming and ridicule phrases, prohibitions against playing and interacting with the opposite sex, and threats and deprivation. Various expressions also emerged that discriminated in behavioral control between males and females. Nonverbal methods included the use of physical punishment and social exclusion as means of directing behavior. The results also showed that current Parental styles of socialization are a direct reflection of social upbringing styles parents experienced during their own childhoods. This indicates the continued use of parenting approaches aimed at controlling social interactions between males and females through both verbal and nonverbal methods. study recommends that parents should adopt a positive approach when dealing with children to enhance their understanding of the social roles of both males and females and the interactions that occur between them. It also encourages fostering children’s social interaction skills within specific behavioral guidelines through group activities and participation in games.